2020
DOI: 10.11606/s1518-8787.2020054003042
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and its impact on immunization programs: reflections from Brazil

Abstract: Due to social distancing guidelines and the displacement of both human and material resources to fight the covid-19 pandemic, individuals seeking healthcare services face certain challenges. Immunization programs have already been a worrisome topic for health authorities due to declines in vaccine uptake rates and are now especially affected by the covid-19 pandemic. Disbelief in science, dissemination of fake news about vaccines, socioeconomic vulnerability and social inequality are some of the challenges fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
1
23
1
7
Order By: Relevance
“…The fact that Brazil is the second most affected country by the COVID-19 pandemic, with a pre-existing economic and political crisis, exacerbated by measures of social restriction to control the pandemic, may be contributing to a dangerous decrease in children’s vaccination coverage. However, the impact of the pandemic on immunization programmes and vaccine uptake among infants in Brazil is not known ( Matos et al, 2020 ). A recent systematic review suggested that this subject has not been studied in Latin America ( Lassi et al, 2021 ).…”
mentioning
confidence: 99%
“…The fact that Brazil is the second most affected country by the COVID-19 pandemic, with a pre-existing economic and political crisis, exacerbated by measures of social restriction to control the pandemic, may be contributing to a dangerous decrease in children’s vaccination coverage. However, the impact of the pandemic on immunization programmes and vaccine uptake among infants in Brazil is not known ( Matos et al, 2020 ). A recent systematic review suggested that this subject has not been studied in Latin America ( Lassi et al, 2021 ).…”
mentioning
confidence: 99%
“…National and international studies attributed a reduction of the population's demand for health services, with a consequent drop in vaccination coverage, to the restrictive mitigation measures adopted during the COVID-19 pandemic [1,5,21,22]. However, there has been an observed trend in a decline in vaccine doses applied in Brazil over the last two decades [22], especially those immunobiologicals recommended in early childhood [13,23].…”
Section: Discussionmentioning
confidence: 99%
“…National and international studies attributed a reduction of the population's demand for health services, with a consequent drop in vaccination coverage, to the restrictive mitigation measures adopted during the COVID-19 pandemic [1,5,21,22]. However, there has been an observed trend in a decline in vaccine doses applied in Brazil over the last two decades [22], especially those immunobiologicals recommended in early childhood [13,23]. Contextual and individual factors that have been cited in recent studies [15,22] have attributed the decline based on vaccination coverage including the lack of planning by the Brazilian National Universal Healthcare System (SUS), social and cultural aspects effecting vaccination acceptance, logistical di culties cited by the PNI in offering several routine vaccines as part of the national vaccine schedule, anti-vaccination movements, and inconsistencies in the availability of immunobiologicals offered by Primary Healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to limitations on the capacity of vaccine production and the global fluctuation in its distribution, it is well-known that several countries around the world have faced enormous challenges in trying to cope with new waves of COVID-19. This is the case experienced by Brazil, a developing country that has suffered from delays in negotiating early deals with pharmaceutical companies [4] and from the high social inequality present in the country [5]. As a consequence, the total number of new cases and deaths significantly increased in 2021, surpassing the worst scenario seen in the previous year [1].…”
Section: Introductionmentioning
confidence: 99%